Conversion of municipal solid waste into 32 MW electricity through pyrolysis a plant design - Asinas, Lovielyn Krystel G.; Giroy, Jose C. Jr.; Jalotjot, Joy Marie G.; Adolacion, Jay R T.; Baynosa, Marjorie L. (Quezon City College of Engineering, University of the Philippines Diliman, 2012)
The production of electricity from municipal solid waste (MSW) is the subject of this proposal. It aims to investigate the economic and technical feasibility of converting 10 tons hour of MSW into 32 MW of electricity through the process of pyrolysis, a chemical decomposition by heat in the absence of oxygen. It is an answer to the increasing solid waste generation and improper management, and also to the increasing need in power supply.The Philippines government set out to restructure and privatize the power sector with the aim of ensuring adequate electricity supply and increasing investment in energy infrastructure. The pyrolysis plant has a market share of 0.84% which indicates the necessity of producing additional source of energy. With the continuous rise of demand of electricity it is projected that by the year 2018, Luzon would need 10,393 MW and for 2030 an increase of 17,636 MW peak demand. This is a direct answer to the Ecological Solid Waste Management Act of 2000, wherein MSW is handled in the most efficient way possible without compromising the quality of wastes produced by the process itself. The plant is located at San Mateo, Rizal specifically near the landfill and beside the river, with land size of 26,803 m3 where minimum cost of production and distribution can be obtained. Waste handling comprises of selling ferrous and nonferrous metals, glass, and filtered ash. Clarifier is utilized for the wastewater treatment and bag house filter is used for air pollution control measures. Process flow is categorized into five major stages of the entire plant: pre-treatment, pyrolysis, syngas cleanup, electricity generation and post-treatment. Pre treatment allows removal of unwanted MSW components such as glass, metals and excess moisture. The pre-treatment MSW will be preheated using spent hot gas from the pyrolyzer. The gas cleanup system is responsible for separating syngas from pyrolysis tar. Syngas is delivered to the gas turbines for electricity generation. To comply with environmental regulations imposed by the government, post treatment methods are to be incorporated in the plant construction. Mass and energy balances are made for all the unit operations and processes. Piping and instrumentation is done to accommodate the four major pipelines in the plant - tar, water, syngas and tar and hot gas streams. For the plant layout, various considerations such as the group pattern scheme for the arrangement of equipment, weather and wind directions and the utility source such as water and air are studied.Detailed equipment design for all the equipment in the plant is also provided. Hazard and operability study is prepared for the pyrolyzer which is the most crucial equipment in the plant. Details such as the industry and technology classification, equipment code, energy source and quantity are identified. The objective, principles and mechanisms, mass balances, important operating conditions, design methodology, design results, process control, energy requirements, equipment cost and manufacturers are included per equipment. Under economic analysis, cost estimation is done through investigation of both fixed and working capital investment, the total production cost, fixed charges, plant overhead costs. General expenses and the product cost, Certain economic parameters and assumptions regarding inflation rates, depreciation, minimum attractive rate of return and taxes are calculated to assess the profitability of the pyrolysis plant. Sensitivity analysis involves evaluation of the breakeven point, Strauss plot and Tornado plot.The net present worth of Php 3585.61 million and Discounted Cash Flow rate of Return of 38.26 percent for profitability measures with time value of money and the end of the year, along with the net present worth of Php 3838.27 million and Discounted Cash Flow rate of Return of 32.39 percent for profitability measures with time value of money with continuous cash flow are obtained. With the payback period of 1.48 years, Return on Investment of 52.97 percent and net return of Php 646.77 million annually, the pyrolysis plant is considered to be feasible and highly profitable.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Organic wastes; Pyrolysis